2005
DOI: 10.1207/s15324796abm3002_9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of patient preference on depression treatment in primary care

Abstract: Obtaining preferred treatment appears to contribute to improved treatment outcome. Continued attempts to assess for and accommodate treatment preferences might result in better response to depression treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 22 publications
7
124
0
3
Order By: Relevance
“…(Davidson et al, 2004). Patient preferences for care are an important facet of retention in, and satisfaction with, psychotherapies (Iacoviello et al, 2007;Lin et al, 2005). Future research should address whether depressive vulnerabilities, similar to those assessed in this and previous studies, do in fact correlate with treatment preferences.…”
Section: Tale 4 About Here Discussionmentioning
confidence: 72%
“…(Davidson et al, 2004). Patient preferences for care are an important facet of retention in, and satisfaction with, psychotherapies (Iacoviello et al, 2007;Lin et al, 2005). Future research should address whether depressive vulnerabilities, similar to those assessed in this and previous studies, do in fact correlate with treatment preferences.…”
Section: Tale 4 About Here Discussionmentioning
confidence: 72%
“…22 Most of our participants reported that they would have liked more say in their choice of treatments. Implementing systems to solicit treatment preferences of persons diagnosed with depression and coordination with counseling resources could substantially improve outcomes given the evidence that providing patients with their preferred mode of treatment increases both treatment uptake and adherence 13,14 and that more patients seem to desire counseling versus medication for treatment of depression. 29 -31 A number of limitations of this study must be acknowledged.…”
Section: Table 5 Participant Statements About Participation In Treatmentioning
confidence: 99%
“…Many persons diagnosed with depression do not commence treatment for it, 9 and the majority of persons who do enter treatment do not receive their preferred type of treatment, even though this seems to lead to better outcomes. 13,14 Furthermore, many persons starting treatment do not complete an adequate treatment course. 15 The US Preventive Services Task Force "recommends screening adults for depression in clinical practices that have systems in place to assure accurate diagnosis, effective treatment, and follow-up" with a grade B recommendation, 16 as such systems have been demonstrated to improve health status and, in some instances, to reduce health care costs.…”
mentioning
confidence: 99%
“…As for psychotherapy, according to Canadian recommendations a minimum of 12 visits are needed, but only 60% of patients having begun psychotherapy receive this much treatment (Duhoux et al, 2012) Under current guidelines, health professionals and, in particular, physicians need to take patient preferences into account in order to encourage adherence and effective treatment of depression (Trivedi et al, 2007;APA, 2000;NICE, 2009). Patients obtaining their preferred treatment (whether psychotherapy or pharmacotherapy) is associated with the best clinical results, particularly in terms of better remission rates but also in terms of a more significant reduction in depressive symptomatology (Clever et al, 2006;Gelhorn et al, 2011;Kocsis et al, 2009;Loh et al, 2007;Lin et al, 2005;Mergl et al, 2011). Persons suffering from depression often have very clear preferences (Churchill et al, 2000;Dwight-Johnson et al, 2000) and want to play an active role in treatment selection (Stacey et al, 2008;Arora and McHorney, 2000).…”
Section: Introductionmentioning
confidence: 99%